2023
DOI: 10.1161/atvbaha.123.319188
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dynamic and Static Analysis of Lymphatic Dysfunction in Lymphedema Using Near-Infrared Fluorescence Indocyanine Green Lymphangiography

Hwayeong Cheon,
Sang-Hun Lee,
Sang Ah Kim
et al.

Abstract: Background: Near-infrared fluorescence indocyanine green lymphangiography, a primary modality for detecting lymphedema, which is a disease due to lymphatic obstruction, enables real-time observations of lymphatics and reveals not only the spatial distribution of drainage (static analysis) but also information on the lymphatic contraction (dynamic analysis). Methods: We have produced total lymphatic obstruction in the upper limbs of 18 Sprague-Dawley rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Furthermore, abnormal waveforms of lymphatic contraction were observed in the CLN dissection group. A previous study showed a change in lymphatic contraction induced by lymphatic obstruction in upper limb lymphedema models 18 . Figure 2C demonstrates a disruption of the cervical lymphatic circulation.…”
Section: Evaluation Of Cln Obstruction and Increased Csf Levelsmentioning
confidence: 87%
See 3 more Smart Citations
“…Furthermore, abnormal waveforms of lymphatic contraction were observed in the CLN dissection group. A previous study showed a change in lymphatic contraction induced by lymphatic obstruction in upper limb lymphedema models 18 . Figure 2C demonstrates a disruption of the cervical lymphatic circulation.…”
Section: Evaluation Of Cln Obstruction and Increased Csf Levelsmentioning
confidence: 87%
“…In addition, we measured lymphatic contraction signals in the same collective lymphatic vessels in both groups. In a previous study, we examined a method for obtaining lymphatic contraction signals through signal processing and identified variations in lymphatic contraction signals caused by lymphatic obstruction 18 .…”
Section: Cervical Edema Evaluation and Nirf-icg Lymphangiographymentioning
confidence: 99%
See 2 more Smart Citations